THE ROLE OF FUNCTIONAL TOP MANAGEMENT TEAM IN INITIATING THE STRATEGIC ALLIANCES AS OUTCOME FROM INNOVATIVENESS BEHAVIOR: EMPIRICAL EVIDENCE FROM STAR HOTELS - Kaihatu, Thomas Stefanus; Oktavio, Adrie (Jurnal Aplikasi Manajemen, 2020)
One way that is widely used by many organizations in general, including hotels to survive in a business competition climate is to encourage employees to have an entrepreneurial mindset and behavior in carrying out their respective functions. The mindset and behavior must, of course, be initiated and supported by the Top Management Team (TMT) including the Functional Top Management Team (FTMT) level. However, unfortunately, some FTMT members do not have the same mindset and behavior. FTMT is like the heart of an organization and functions as a predecessor from the birth of a business strategy such as strategic alliances. In the context of hotels, strategic alliances should ideally be born from innovative ideas that are not only the responsibility of FTMT. Thus, FTMT must also play a role to encourage the creation of innovation that is in line with the organization's vision, mission, goals, and competencies. Improving the entrepreneurial orientation of the hotel, especially the innovativeness factor is an important step to initiate the application of statistic alliances which of course the strategy should come from the ideas of the FTMT. This study tries to analyze the role of FTMT and its influence on innovation and the application of business strategies in the form of strategic alliances. Data collected from 29 4 and 5 star hotels in Surabaya were analyzed using structural equation modeling to support the hypothesis of this research. The results of this study indicate that all three hypotheses can be accepted where FTMT influences innovativeness and strategic alliance. Innovativeness also has a direct influence on strategic alliances.